Fabrication of palatable medicated chocolate of salbutamol and ambroxol for pediatric delivery - Gayathri Rajaram (Journal of Global Pharma Technology, 2020)
Chocolate as a dosage form is the most adaptable and versatile form that attracts children of all age groups. The present research work is to design and fabricate a palatable medicated chocolate to deliver salbutamol and ambroxol for pediatric care or prescription. Preformulation studies such as DSC, FTIR, melting point and solubility were carried out to detect any incompatibility and purity of the drugs. Medicated chocolate was formulated by incorporating the drugs into the chocolate base, with desirable viscosity. Three formulations were prepared and evaluated for physical appearance, drug excipient compatibility, weight variation, thickness, drug content, in-vitro drug release, bloom strength, stability and release kinetics. The parameters were within official specifications for formulation F3. The in-vitro drug release for optimal formulations is 86.7% and 89.4% for salbutamol and ambroxol, respectively and followed zero-order kinetics and fickian transport from the dosage form. No significant changes in the physical and chemical properties were observed during stability studies, which indicate that the formulated medicated chocolate was stable and could ensure a good therapeutic effect with patient compliance. The fabricated chocolate was elegant, smooth and creamy in texture and was excellent for taste masking unpleasant flavors associated with the drugs and excipients. The formulated chocolate may improve patient compliance as it can be used easily by pediatric patients with high preference. Keywords: Ambroxol, Chocolate delivery, Mucolytic, Bronchodilator, Salbutamol, Pediatric